Análise da prática interprofissional colaborativa no Serviço de Obesidade e Cirurgia Bariátrica do Hospital Universitário do Oeste do Paraná - Frank, Thais Cristina da Silva (2021)
According to the Ministry of Health and the Pan American Health Organization, to address and improve the quality of care for chronic noncommunicable diseases - including obesity - it is necessary to organize health professionals into multidisciplinary teams working in an interprofessional manner. In this context, the Obesity and Bariatric Surgery Service of the Hospital Universitário do Oeste do Paraná, located in Cascavel, serves obese individuals in the region, providing assistance in group format with a multiprofessional team. The need then arose to verify whether there is interprofessional care in the multidisciplinary team that operates there, as well as whether the environment and the performance of the team favor collaborative interprofessional practices in the care of the obese individual, this being the aim of the study. It was possible to identify and evaluate the existence and level of collaborative practice in the team through the use of two research tools: the RIPLS questionnaire already validated in Brazil, for the quantitative part and an interview through a semi-structured questionnaire for the quantitative part of the research. Participated in this study, the twelve fixed health professionals of the team, being the majority female (75%), with a mean age of 46 years, who had worked, in average, for 4.2 years in the service. The results showed that there is a favorable environment for the interprofessional practice in the Obesity and Bariatric Surgery Service of the Western Paraná University Hospital. Although some points need improvement, especially related to the definition of flows for adequate formalization of documents, it was concluded that the team acts at a high level of collaborative practice, having, therefore, more strengths than weaknesses.